NB Theory with Bargaining Problem: A New Theory - Noorulden Basil Mohamadwasel; Alfian Ma'arif (Association for Scientific Computing Electronics and Engineering (ASCEE), 2022)
A new theory is proposed to achieve desired set of values for an engineering system based on a single algorithm that consists of all optimization algorithms. This algorithm considers an engineering system's main variables, dimensions, and functions; all these parameters will be set and tuned by a systematic search in the main library. This single algorithm automatically selects an optimization algorithm suitable for a particular optimization problem. Additionally, this theory, which was inspired by the idea of bargaining theory and Noorulden Basil theory, referred to as NB Theory, can be done using MATLAB Software.